A novel in vitro 3D model of the human bone marrow to bridge the gap between in vitro and in vivo genotoxicity testing. (8th April 2022) - Vernon, Alexander R; Pemberton, Roy M; Morse, H Ruth
Abstract: The regulatory 2D in vitro micronucleus (MN) assay is part of a battery of tests, used to test for genotoxicity of new and existing compounds before they are assessed in vivo (ICH S2). The 2D MN assay consists of a monolayer of cells, whereas the in vivo bone marrow (BM) setting comprises a multicellular environment within a three-dimensional extracellular matrix. Although the in vitro MN assay follows a robust protocol set out by the Organisation for Economic Co-operation and Development (OECD) to comply with regulatory bodies, some compounds have been identified as negative genotoxicants within the in vitro MN assay but marginally positive when assessed in vivo . The glucocorticoids, which are weakly positive in vivo, have generally been suggested to pose no long-term carcinogenic risk; however, for novel compounds of unknown activity, improved prediction of genotoxicity is imperative. To help address this observation, we describe a novel 3D in vitro assay which aims to replicate the results seen within the in vivo BM microenvironment. AlgiMatrix scaffolds were optimized for seeding with HS-5 human BM stromal cells as a BM microenvironment, to which the human lymphoblast cell line TK6 was added. An MN assay was performed aligning with the 2D regulatory assay protocol. Utilizing this novel 3D in vitro model of the BM, known genotoxicants (mitomycin C, etoposide, and paclitaxel), a negative control (caffeine), and in vivo positive glucocorticoids (dexamethasone and prednisolone) were investigated for the induction of MN. It was found, in agreement with historical in vivo data, that the model could accurately predict the in vivo outcome of the glucocorticoids, unlike the regulatory 2D in vitro MN assay. These preliminary results suggest our 3D MN assay may better predict the outcome of in vivo MN tests, compared with the standard 2D assay.